2007
DOI: 10.1088/0031-8949/75/3/005
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric scintillations on 3.925 GHz signal from Intelsat (701) at low latitude in the South Pacific region

Abstract: The morphological features of initial ionospheric scintillations on 3.925 GHz beacon signal from geostationary satellite Intelsat (701) at Suva (Lat., 18.08° S, Long., 178.3° E, Geom. Lat., 22.1° S), Fiji, a low latitude station in the South Pacific region have been studied during the period of December 2003 to June 2004. Scintillations were, in general, sparse, of which activity was more pronounced in the daytime. Scintillation occurrence was less in general, showing a peak value of about 2.5% at 09 h LT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This theory has proven to work well in the midlatitude, where the inclination angle (I) is steep enough to produce Es layers (Whitehead, , ). Evidence regarding the midlatitude (Hajkowicz, , ; Hajkowicz & Minakoshi, ; Ogawa, Suzuki, & Kunitake, ), low latitude, and equatorial regions (Alfonsi et al, ; Huang, ; Kumar et al, ; Patel et al, , ; Seif et al, , , , ; Zou & Wang, ; Zou, ) have shown correlation between the occurrence of daytime scintillation and the Es layer. Nevertheless, thus far, very little is known about the nature of daytime L‐band scintillations and characteristics of Es at the magnetic dip equator, where wind shear theory fails to operate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory has proven to work well in the midlatitude, where the inclination angle (I) is steep enough to produce Es layers (Whitehead, , ). Evidence regarding the midlatitude (Hajkowicz, , ; Hajkowicz & Minakoshi, ; Ogawa, Suzuki, & Kunitake, ), low latitude, and equatorial regions (Alfonsi et al, ; Huang, ; Kumar et al, ; Patel et al, , ; Seif et al, , , , ; Zou & Wang, ; Zou, ) have shown correlation between the occurrence of daytime scintillation and the Es layer. Nevertheless, thus far, very little is known about the nature of daytime L‐band scintillations and characteristics of Es at the magnetic dip equator, where wind shear theory fails to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Es can occur during daytime and nighttime. The occurrence of daytime Es can result in strong ionospheric scintillations (Aarons, 1982) even in the frequency range of gigahertz (GHz) (Kumar, Kishore, & Ramachandran, 2007;Seif et al, 2015;Zou, 2011;Zou & Wang, 2009). That is, during daytime, scintillation-producing irregularities are requiring a steep gradient associated with the background plasma-density profile, and a current driven by a neutral wind, where the Es layer is presumed to provide the exceptionally steep gradient particularly in the midlatitude.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, daytime GHz scintillation studies attracted as much attention as nighttime scintillation studies, perhaps because daytime scintillation have a relatively lower rate of occurrence and milder nature (Patel et al 2009). For the most part, scintillations are generally believed to be associated with the F layer at night and the blanketing sporadic E (E sb ) layer during the day (Kumar et al 2007;Zou and Wang 2009;Zou 2011;Seif et al 2012;Alfonsi et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a few observations of scintillation in the range of GHz have been also investigated for low latitudes. For example, Kumar et al (2007) used radio transmissions from geostationary satellite Intelsat to determine scintillations at 3.925 GHz at Suva, Fiji (18.08°S, 178.3°E; dip latitude (Ф) = 22.55°S). They showed that scintillation was more pronounced during the daytime.…”
Section: Introductionmentioning
confidence: 99%